Newborn Safety in the Hospital. Issue 4 (July 2015) - Simpson, Kathleen Rice
Abstract : More focus is needed on the safety of newborns while in the care of their parents on the mother-baby unit to prevent babies from being accidently injured. Promotion of breastfeeding and maternal-newborn attachment should be in the context of newborn safety.